Transmission of SARS-CoV-2 in Domestic Cats - Halfmann, Peter J; Hatta, Masato; Chiba, Shiho; Maemura, Tadashi; Fan, Shufang; Takeda, Makoto; Kinoshita, Noriko; Hattori, Shin-ichiro; Sakai-Tagawa, Yuko; Iwatsuki-Horimoto, Kiyoko; Imai, Masaki; Kawaoka, Yoshihiro (The New England journal of medicine, 2020)
SARS-CoV-2 was detected in three cats after they were cohoused with cats that had been experimentally inoculated with the virus. Cats may be a silent intermediate host of SARS-CoV-2.